2003
DOI: 10.1021/jm030888c
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazole Derivatives as Partial Agonists for the Nicotinic Acid Receptor

Abstract: Nicotinic acid as a hypolipidemic agent appears unique due to its potential to increase HDL cholesterol levels to a greater extent than other drugs. However, it has some side effects, among which severe skin flushing is the most frequent and often limits patients' compliance. In a search for novel agonists for the recently identified and cloned G protein-coupled nicotinic acid receptor, we synthesized a series of substituted pyrazole-3-carboxylic acids that proved to have substantial affinity for this receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 21 publications
2
44
0
1
Order By: Relevance
“…Several pharmaceutical companies began developing selective agonists of GPR109A (42)(43)(44)(45)(46)(47). Walters et al ( 48 ) suggested that the effects of niacin on FFAs and fl ushing could be segregated.…”
Section: Niacin Receptormentioning
confidence: 99%
“…Several pharmaceutical companies began developing selective agonists of GPR109A (42)(43)(44)(45)(46)(47). Walters et al ( 48 ) suggested that the effects of niacin on FFAs and fl ushing could be segregated.…”
Section: Niacin Receptormentioning
confidence: 99%
“…A series of pyrazole-3-carboxylic acids has been reported as partial agonists for the nicotinic acid receptor 117 aimed to treat atherosclerosis. It was postulated that partial agonism might result in tissue selectivity.…”
Section: Carboxylic Acidsmentioning
confidence: 99%
“…119 Other pyrazoles with anti-lipidemic activity are compounds 117 and 118. 117 It has been postulated that compared to full agonists, partial agonists may exhibit reduced adverse effects. Interestingly, compound 117, a partial agonist in the GTPgS (guanosine 5'-O-[-thio]triphosphate) assay, turned out to be a full agonist in the cAMP whole-cell assay.…”
Section: Carboxylic Acidsmentioning
confidence: 99%
“…Preliminary studies demonstrate that Lp(a) levels may be reduced with niceritrol (a niacin prodrug), plasma apheresis and renal transplantation 30 . In addition, pyrazole derivatives as partial agonists for the nicotinic acid receptor may be future therapeutic targets for decreasing Lp(a) levels 31 .…”
Section: Lipoprotein (A)mentioning
confidence: 99%